New Record for the Flora of Iraq: Myosotis incrassata Guss. (Boraginaceae) - Hiwa Hussein Hasan; Abdullah Shakur Sardar (Zanco Journal of Pure and Applied Sciences, 2025)
The genus Myosotis incrassata Guss. is one of the largest genera of tribe Myosotideae, subfamily Cynoglossoideae, and family Boraginaceae. The aim of this study is to validate the M. incrassata is new record in Iraq, so that an extensive sampling characterization of macro- and micro-morphology, some characteristics of pollen grains, such as shape, color, size, sculpture, and number have been studied. To further validate the taxonomic position of M. incrassata within the Boraginaceae family, phylogenetic analyzes have been performed. The collected plant specimens differ from the other species that are already present in Iraq, where M. incrassata differs from others in that the calyces in fruit are rarely appressed, less than 3 mm, and not crowded. Pollens was yellow in color, single, 3-colporate, circular in equatorial view, spheroid in polar view, small-sized. The molecular studies have confirmed the genetic relationship and placement of this newly recorded species within the broader context of the family, solidifying its classification and evolutionary lineage.